Developmental coordination disorder - Hyde, C.; Rigoli, Daniela; Piek, Jan (2017)
Historically, Developmental Coordination Disorder (DCD) has perhaps been the most poorly recognized of the neurodevelopmental disorders. As we will canvass in this chapter, the reasons are complex and varied, ranging from considerable variation in the application of diagnostic labelling and criterion, to issues surrounding the appropriateness of assessment methods and the frequent comorbid presentation of DCD with other neurodevelopmental disorders. However, there is a growing awareness of the serious impact that delayed motor development has on the dayto-day lives of these individuals and their broader psycho-social and physical development. While the genetic basis of the disorder has received little attention, the available evidence nonetheless suggests a shared role for familial and environmental factors. Neuropsychological models of the disorder have received greater attention and here we review two particularly promising accounts of motor delay, including impaired internal modelling and executive dysfunction. While each is supported by empirical evidence to some degree, their efficacy will ultimately be judged by their capacity to inform effective treatment. Presently, evidence to this effect is largely lacking. Interestingly, although investigation into the neuropathology of DCD has only recently emerged, there is a strong case that atypical neural activation, white matter microstructure and neural connectivity in critical motor circuitry differentiate children with DCD from typical peers. The suggestion of neural markers for the disorder is interesting, given that neurological impairment is presently an exclusionary criterion for DCD. Taken together, however, despite the continued focus on better understanding the aetiology of DCD, no universal account has emerged. It is perhaps unsurprising then, that evidence as to the efficacy of available intervention methods is mixed, at best.